EFFECT OF TAI CHI AND AEROBIC EXERCISE PROGRAM ON MUSCULAR STRENGTH, BALANCE AND QUALITY OF LIFE IN ELDERS - Smuntavekin, Sudpranorm; Kittichotpanich, Boonsri; Chawpreecha, Oranuch (JOURNAL OF THE POLICE NURSES AND HEALTH SCIENCE, 2021)
This quasi-experimental research aimed to compare the effects of a tai chi and aerobic training program on the muscular strength and balance of the elders. The samples were 66 elders participating in health promotion program at Sirinthorn hospital, Prawet, Bangkok. Then, they were equally divided into two groups, 33 subjects for each group which were the control group and the experimental group. The experimental group was added tai chi to the exercise for 50 minutes daily, 3 times a week, and maintained the routine for 8 weeks. The criterion standard of the fitness test was supported by the department of physical education measuring muscular strength and balance using a single leg stand and foot-to-foot test at the beginning and after 8 weeks of the program. Data were analyzed by mean and standard deviation. The differences in the leg muscular strength and balance were tested by using paired t-test and independent t-test. Data from the interview were analysed using content analysis. The results showed that 1) the experimental group who received the tai chi and aerobic program had significantly different improvements in muscular strength and balance than the control group at the level of .05, 2) the experimental group had a better quality of life in physical, psycho-emotional, social, and environmental aspects than the control group. In conclusion, the tai Chi and aerobic exercise program was able to improve leg muscular strength and balance, which could reduce the risk of falling. It was also able to raise the quality of life in elderly people.